2018
DOI: 10.1007/s11116-018-9964-6
|View full text |Cite
|
Sign up to set email alerts
|

Does the accessibility measure influence the results of residential location choice modelling?

Abstract: Accessibility is essential in Land-Use Transport Interaction (LUTI) framework. For residential location choice in particular, it has always been important at theoretical level. At empirical level, the place of accessibility is doubt in some case studies, considering other location characteristics more important, like the social environment and the neighbourhood amenities. However, this result can be caused by the measurement of accessibility. In view of the wealth of approaches, this paper examines whether dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
1
9
1
Order By: Relevance
“…In the model developed in this study, these variables are highly significant. This finding is consistent with the conclusions of a recent study conducted by Baraklianos et al (2020), who found accessibility factors to be of importance in their residential location choice model in the Lyon metropolitan area in France [35]. The relations between residential location choice and accessibility of work place and different types of services have also been shown in the Stockholm region, Sweden [36], though in this model, Eliasson did not categorize the location choices into mobility and non-mobility.…”
Section: Discussionsupporting
confidence: 90%
“…In the model developed in this study, these variables are highly significant. This finding is consistent with the conclusions of a recent study conducted by Baraklianos et al (2020), who found accessibility factors to be of importance in their residential location choice model in the Lyon metropolitan area in France [35]. The relations between residential location choice and accessibility of work place and different types of services have also been shown in the Stockholm region, Sweden [36], though in this model, Eliasson did not categorize the location choices into mobility and non-mobility.…”
Section: Discussionsupporting
confidence: 90%
“…In some of the studies conducted in the developed world, social interactions and neighbors with similar socioeconomic backgrounds have also been a significant factor in residential location choices [14]. Other important determinants of residential location choices have been reported as the quality of schools [15], accessibility to services and jobs [16,17], mobility attitudes, the built environment [18][19][20][21][22], and the affordability and neighborhood characteristics [23,24].…”
Section: Correlates Of Residential Location Choicesmentioning
confidence: 99%
“…Several studies have focused on distinct aspects when addressing the issue of residential location models [14][15][16][17][18][19][20][21][22]. A substantial amount of research investigates the role of transportation systems and transportation accessibility on location choice [1,12,16,17,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on distinct aspects when addressing the issue of residential location models [14][15][16][17][18][19][20][21][22]. A substantial amount of research investigates the role of transportation systems and transportation accessibility on location choice [1,12,16,17,[24][25][26][27][28]. Most of these studies discussed how households choose between different residential locations and considered changes in transportation, level of service, and neighborhood quality as significant variables.…”
Section: Introductionmentioning
confidence: 99%